Priming of Salmonella enterica serovar typhi-specific CD8(+) T cells by suicide dendritic cell cross-presentation in humans. - Rosângela Salerno-Goncalves; Marcelo B Sztein (PLoS ONE, 2009)
BACKGROUND:The emergence of antibiotic-resistant strains of Salmonella enterica serovar Typhi (S. Typhi), the etiologic agent of typhoid fever, has aggravated an already important public health problem and added new urgency to the development of more effective typhoid vaccines. To this end it is critical to better understand the induction of immunity to S. Typhi. CD8(+) T cells are likely to play an important role in host defense against S. Typhi by several effector mechanisms, including killing of infected cells and IFN-gamma secretion. However, how S. Typhi regulates the development of specific CD8(+) responses in humans remains unclear. Recent studies in mice have shown that dendritic cells (DC) can either directly (upon uptake and processing of Salmonella) or indirectly (by bystander mechanisms) elicit Salmonella-specific CD8(+) T cells. METHODOLOGY/PRINCIPAL FINDINGS:We report here that upon infection with live S. Typhi, human DC produced high levels of pro-inflammatory cytokines IL-6, IL-8 and TNF-alpha, but low levels of IL-12 p70 and IFN-gamma. In contrast, DC co-cultured with S. Typhi-infected cells, through suicide cross-presentation, uptake S. Typhi-infected human cells and release high levels of IFN-gamma and IL-12p70, leading to the subsequent presentation of bacterial antigens and triggering the induction of memory T cells, mostly CD3(+)CD8(+)CD45RA(-)CD62L(-) effector/memory T cells. CONCLUSIONS/SIGNIFICANCE:This study is the first to demonstrate the effect of S. Typhi on human DC maturation and on their ability to prime CD8(+) cells and highlights the significance of these phenomena in eliciting adaptive immunity to S. Typhi.